If it's not what You are looking for type in the equation solver your own equation and let us solve it.
y-4=6
We simplify the equation to the form, which is simple to understand
y-4=6
We move all terms containing y to the left and all other terms to the right.
+1y=+6+4
We simplify left and right side of the equation.
+1y=+10
We divide both sides of the equation by 1 to get y.
y=10
| h+4/9=7/9 | | 7.4+d=-18.62 | | m-9.78=65.32 | | 6.3+k=12.5 | | b/4+10=13 | | 16+2a=-2(3a-4) | | 11-4x=6+x | | 4c+0=48 | | 3g-1+2g+8=g+2 | | A=5i+7j | | u+6=v | | -5+3x+3+2= | | -2(7-4)+4=-4 | | 7a=15a-80 | | 15y-12y=24 | | 0.02=100 | | 20y^7v^8u^2= | | 3(-2+x)=-24 | | 2b-6-3b-b= | | 10+7x=5x-6 | | (2x-1)(x+3)=(x-3)(x+1) | | 3x+21=68 | | -72-11c+6c^2=0 | | -4-5=3-3x+4x | | -2x-1=-(2x+3) | | -17+8v=-6v-5(2-3v) | | 32-4(6)(42)=0 | | 2x^2+4x-21=24-9x | | 9x-7=2x+3 | | 12(x+13)=252 | | 3+m+(-1m)= | | -8.07=d-4.48 |